Design thinking in managing the dynamics of group intellectual work - E. V. Vasilieva (Управление)
The use of design thinking for the formation of soft skills of specialists has been proved in the article. Presently, the concept of Π-shaped competence takes on a new meaning: a modern specialist needs professional competencies and soft skills, and especially empathy and willingness to cooperate. The purpose of this work is to show the role of the design thinking approach in the development of soft skills among specialists.The design thinking approach is currently developing in three main areas: the methodology for research and  improvement of customer experience (service design), the basis for team building and corporate culture growth (as part of employee experience management), and neuro-design. A portfolio of tools included in a well-defined design solution structure helps guide the creative team to effectively use their cognitive abilities, which ultimately allows them to find a breakthrough innovative solution.Based on the author’s own experience in teaching design thinking to University students and students of business programs, the rules for conducting design seminars for discussion have been proposed. The main areas of application of design thinking have been highlighted and described in the cases: creating an innovative product that is in demand by the consumer; improving the processes of organization and team building, personal growth and creativity development. Features of design seminars have been shown, descriptions of  some popular design thinking techniques have been given (empathy map, CJM, HMW, CBF, World café), and the author’s addition to the user’s path map – the PEdPL model has been presented. The impact of various design thinking techniques on the results of group work has been assessed. The curve of emotions and performance of the group during the design session in the training format has been constructed. Recommendations for managing the dynamics of group work using design thinking techniques and coaching techniques have been given.